MILINEAL GENERATION INTENTION IN INVESTING SHARIA-BASED MUTUAL FUNDS DIGITAL - Permatasari, Ayu; Hermawan Adinugraha, Hendri (Studia Economica : Jurnal Ekonomi Islam, 2023)
The purpose of this study is to describe the intention of the millennial generation to invest in digital-based Islamic mutual funds. This study uses a type of descriptive-analytical research. The findings in this study are that investors in the capital market have experienced a significant increase, and this increase is dominated by the millennial generation who are under 30 years old. One of the investment instruments that is widely used by the millennial generation is sharia mutual funds. Various factors influence the intention of the millennial generation to invest in digital-based sharia mutual funds, including 1) Financial Literacy where the millennial generation is now more sensitive to financial literacy, this is due to technological developments from year to year that are so fast, 2) Personal Interest from the millennial generation who want to invest in digital-based sharia mutual funds 3) Technological developments allow everyone to obtain and access various kinds of information about investments. For this reason, current technological advances have created the desire or intention of the millennial generation to invest in Islamic mutual funds using digital platforms.